Regulation of aggregation-induced emission color of α-cyanostilbene luminogens through donor engineering of amino derivatives. (13th April 2021) - Tonga, Murat
Graphical abstract: α-cyanostilbene inserted D-π-A-π-D molecules containing various substituents on the amino donor group (e.g., π-conjugated, aryl/alkyl, and dialkyl) were designed, synthesized and their aggregation-induced emission (AIE) was investigated thoroughly. The incorporation of these substituents resulted in tunable emission colors ranging from green-to-yellow-to-red. Highlights: A series of D-π-A-π-D type α-cyanostilbene luminogens were synthesized. The effects of the substituents on amino donor groups were studied thoroughly. AIE properties with tunable emission colors ranging from green-to-yellow-to-red were achieved. DFT calculations allowed the understanding of the relationship between structures and the AIE properties. Abstract: In this contribution, α-cyanostilbene-based D-π-A-π-D type compounds consisting of different substituents on the amino donor group (e.g., fused, aryl/alkyl, and dialkyl) were designed, synthesized and their aggregation-induced emission was investigated thoroughly. The incorporation of these substituents furnished AIE features with tunable emission colors ranging from green-to-yellow-to-red. The compounds all showed a weak emission in THF; however, they showed an enhanced emission upon addition of water by forming emissive aggregates, which may arise from the restriction of twisted intramolecular charge transfer and E / Z isomerization. The DFT calculations revealed that the luminogens adopted distinctive conformations including a highly twisted one and a relatively coplanar one with the variation in the amino substituents.